Type of maxillary segment mobilization affects three-dimensional nasal morphology. Issue 3 (March 2021) - Denadai, Rafael; Chou, Pang-Yun; Lin, Yi-Yu; Yao, Chuan-Fong; Chen, Ying-An; Huang, Chiung-Shing; Lo, Lun-Jou; Chen, Yu-Ray
Summary: Background: Surgical mobilization of the maxillary segment affects nasal morphology. This study assessed the impact of the type of maxillary mobilization on the three-dimensional (3D) nasal morphometry. Methods: Pre- and postsurgery cone beam computed tomography-derived facial image datasets of consecutive patients who underwent two-jaw orthognathic surgery were reviewed. Using preoperative 3D facial models as the positional reference of the skeletal framework, 12-month postoperative 3D facial models were classified into four types of maxillary mobilizations (advancement [ n  = 83], setback [ n  = 24], intrusion [ n  = 55], and extrusion [ n  = 52]) and four types of final maxillary positions (anterosuperior [ n  = 44], anteroinferior [ n  = 39], posterosuperior [ n  = 11], and posteroinferior [ n  = 13]). Six 3D soft tissue nasal morphometric parameters were measured, with excellent intra- and interexaminer reliability scores (ICC>0.897) for all the measurements. The 3D nasal change for each nasal parameter was computed as the difference between postoperative and preoperative measurement values. Results: The intrusion maxillary mobilization resulted in a significantly (all p <0.05) larger 3D nasal change in terms of alar width, alar base width, and nostril angle parameters, and a smaller change in terms of the nasal tip height parameter than the extrusion maxillary mobilization; however, no significant (all p >0.05) difference was observed between advancement and setback maxillary mobilizations. The anterosuperior and posterosuperior maxillary positions had a significantly (all p <0.05) larger 3D nasal change in terms of the alar base width and nostril angle than the anteroinferior and posteroinferior maxillary positions. Conclusion: The type of maxillary mobilization affects the 3D nasal morphometry.